Fepas: proposta de ferramenta auxiliar para o ensino de projeto arquitetônico visando a promoção da sustentabilidade - Barros, Joana D'arc Pereira de (2023)
Architects and urban planners can contribute to the promotion of sustainable development and to the mitigation of environmental, social, and economic impacts. For this purpose, it is necessary that, during their formative years, the concept of sustainability is reinforced, especially in the university courses dedicated to project development that structure the Architecture and Urbanism curriculum. Therefore, the main purpose of the research was to develop an auxiliary tool for teaching architectural design that encourages students and teachers to use the principles of sustainability, both in the process of developing the design exercise and in the assessment of academic work. Thus, the following specific objectives were established: 1) To identify the main characteristics of the teaching of Architecture and Urbanism, especially in the academic activities of the so-called “design studio”, and its relation with the contents of sustainability; 2) Select and adapt sustainability indicators commonly used in assessment tools available on the market, and which can be used in teaching project design; 3) Create an auxiliary tool for teaching architectural design that can also be used in the assessment process of projects developed by students; 4) Indicate teaching and learning strategies for the application of the tool and; 5) Test the applicability of the proposed tool and evaluate the results. The research involved the analysis of curricula of referential Architecture and Urbanism courses in Brazil; the selection and adaptation of sustainability indicators; the development of a theoretical framework with indicators, project strategies and benchmarks to define how each indicator should be evaluated; and the structuring of the tool in a spreadsheet with weights suggested from the results of a questionnaire applied to professors from institutions in all regions of Brazil. The proposed tool – FEPAS – has 6 categories and 17 indicators. The questionnaire had the participation of 117 professors working in institutions from different regions of Brazil and demonstrated that the FEPAS indicators can be applied in project teaching and that they must have different levels of relevance. FEPAS is expected to assist teachers in conducting project teaching and in adopting objective criteria for evaluating the works developed by students, reducing the subjective tendency traditional in the atelier, as well as being effective in raising awareness and training future architects and urban planners.